Variants in the CETP gene affect levels of HDL cholesterol by reducing the amount, and not the specific lipid transfer activity, of secreted CETP - Ølnes, Åsa Schawlann; Teigen, Marianne; Laerdahl, Jon K.; Leren, Trond P.; Strøm, Thea Bismo; Bjune, Katrine (PloS one, 2023)
Cholesteryl ester transfer protein (CETP) transfers cholesteryl esters in plasma from high density lipoprotein (HDL) to very low density lipoprotein and low density lipoprotein. Loss-of-function variants in the CETP gene cause elevated levels of HDL cholesterol. In this study, we have determined the functional consequences of 24 missense variants in the CETP gene. The 24 missense variants studied were the ones reported in the Human Gene Mutation Database and in the literature to affect HDL cholesterol levels, as well as two novel variants identified at the Unit for Cardiac and Cardiovascular Genetics, Oslo University Hospital in subjects with hyperalphalipoproteinemia. HEK293 cells were transiently transfected with mutant CETP plasmids. The amounts of CETP protein in lysates and media were determined by Western blot analysis, and the lipid transfer activities of the CETP variants were determined by a fluorescence-based assay. Four of the CETP variants were not secreted. Five of the variants were secreted less than 15% compared to the WT-CETP, while the other 15 variants were secreted in varying amounts. There was a linear relationship between the levels of secreted protein and the lipid transfer activities (r = 0.96, p<0.001). Thus, the secreted variants had similar specific lipid transfer activities. The effect of the 24 missense variants in the CETP gene on the lipid transfer activity was mediated predominantly by their impact on the secretion of the CETP protein. The four variants that prevented CETP secretion cause autosomal dominant hyperalphalipoproteinemia. The five variants that markedly reduced secretion of the respective variants cause mild hyperalphalipoproteinemia. The majority of the remaining 15 variants had minor effects on the secretion of CETP, and are considered neutral genetic variants.